The Influence of Role Model and Social Media on Alertness to Business Ideas Among Gen Z - Mohammad Yuki Fairuuz; Keumala Hayati (Yayasan pendidikan dzurriyatul Quran, 2026)
This study examines how role models and social media influence alertness to business ideas among Generation Z in Bandar Lampung. Alertness to Business Ideas (ABI) is an early-stage entrepreneurial capability that enables individuals to notice, interpret, and evaluate information that may develop into potential opportunities. This research aims to determine whether exposure to role models and engagement with social media significantly strengthen ABI among young individuals. A quantitative approach was used, involving 150 valid responses collected from Generation Z participants. Data were analyzed using descriptive statistics, validity and reliability testing, and multiple linear regression with a Bootstrap resampling procedure of 5000 iterations. The findings show that respondents reported high perceptions of role models, strong social media engagement, and high levels of alertness to business ideas. The regression results indicate that both role models and social media have a significant positive effect on ABI, with role models demonstrating the stronger influence. The model explains 45.6 percent of the variance in ABI. These findings suggest that role models and social media both play important roles in shaping alertness to business ideas among youth. The study implies that strengthening students’ exposure to entrepreneurial role models and enhancing access to informative digital content may further develop their ability to notice, interpret, and evaluate potential business opportunities.